2018
DOI: 10.1038/aps.2017.147
|View full text |Cite
|
Sign up to set email alerts
|

Emodin alleviates alternatively activated macrophage and asthmatic airway inflammation in a murine asthma model

Abstract: Alternatively activated macrophages (AAMs) are not only associated with asthma but also lead to asthmatic airway inflammation and remodeling. Inhibition of AAMs is an alternative therapeutic strategy for treating asthma. In this study we investigated whether emodin (1,3,8-trihydroxy-6-methylanthraquinone), isolated from the rhizome of Rheum palmatum, alleviated asthmatic airway inflammation and reduced AAM polarization in a murine asthma model. Mice were sensitized with a triple allergen mix containing dust mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Scientists have explored the differences in structure and abundance of the intestinal micro ora under healthy and disease conditions to identify the role of the gut microbiota during disease development. Dysbiosis in the gut micro ora also occurs in many disorders [15][16][17]. ALI activated the systemic in ammatory response and secretion of in ammatory mediators, leading to intestinal mucosal barrier damage and intestinal bacterial translocation, which affected the intestinal ora diversity, distribution and composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists have explored the differences in structure and abundance of the intestinal micro ora under healthy and disease conditions to identify the role of the gut microbiota during disease development. Dysbiosis in the gut micro ora also occurs in many disorders [15][16][17]. ALI activated the systemic in ammatory response and secretion of in ammatory mediators, leading to intestinal mucosal barrier damage and intestinal bacterial translocation, which affected the intestinal ora diversity, distribution and composition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rhubarb regulated the gut microbiota and protected against ALI. Emodin, extracted from rhubarb, has shown anti-in ammatory properties for treating pancreatitis, atherosclerosis, asthma, and ALI [15][16][17]. Xiao et al indicated that emodin relieved pulmonary edema and MCP-1 and E-selectin secretions and inhibited LPS-induced pulmonary damage [17].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage activation is not only associated with the airway inflammatory response but also with airway remodeling ( 39 ), and cell-derived MCP-1 acts as a potent eosinophil chemoattractant ( 40 , 41 ). Therefore, the regulation of macrophage activation and overproduction of MCP-1 is an alternative therapeutic strategy for treating allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Aloe vera extract can downregulate TNF‐α, IL‐1β and IL‐6 expression in macrophages in a mouse model of lipopolysaccharide (LPS)‐induced acute lung injury (ALI), thus potentially protecting LPS‐induced ALI . Other extracts used in traditional Chinese medicine, such as curcumin, emodin, berberine and grass coumarone, have similar effects. Most of the traditional Chinese medications that inhibit tumours have “promoting blood stasis, reducing swelling and dispersing” effects.…”
Section: Exogenous Inducers Of Macrophage Heterogeneitymentioning
confidence: 99%